Development of Schoology-based E-Learning on Ion Equilibrium and pH of The Buffer Solutions - Linda, Roza; Sukma, Suci; Anwar, Lenny (JTK (Jurnal Tadris Kimiya), 2021)
This study aims to develop a Schoology-based e-learning media and to find out the validity and response of users (teachers and students). The method used in this research was Research and Development (R&D) with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The implementation stage was not carried out due to the limitations of the research. Validation tests carried out by material and media experts as well as limited trials on students and teachers were obtained using a questionnaire. The data analysis technique used was descriptive analysis. The validation results from material and media expert showed the percentage of 93.23% and 90.69% in the valid category. The results of trial by student and teacher responses showed the percentage of 94.40% and 93.12% in good category. The Schoology-based e-learning media on ion equilibrium and buffer solutions is valid and suitable for use in online learning. Â